Application of additive manufacturing in Forensic Sciences: new technologies at the service of justice and society (Research, Society and Development, 2023)
In Forensic Sciences, additive manufacturing technology has been used for some years as a tool to assist in the process of human identification. The possibility of printing important evidence, such as weapons used in crimes, objects, bones, teeth and body remains, becomes interesting, as it reduces the need to move and handle the original evidence. However, as it is a recent method, analyzes and standardization are necessary to verify the best printing technique for each case. In order to verify what is in literature about the use of additive manufacturing in Forensic Sciences and in the process of human identification, an integrative literature review was carried out in different databases on the use of 3D printing in Forensic Sciences and in the human identification process, using the terms “3D print and forensic sciences”, “3D print and forensics”, addictive manufacturing and forensics”, “3D print and human identification” and “addictive manufacture and human identification”; the period from 2017 to 2022 was established. Although 3D printing seems to be obtained in a singular way, its manufacture can be carried out in different ways, but this diversity does not affect the reliability of the print. Weapons, bones, teeth, wounds, projectile trajectories, fingerprints or organs, among others, are reproduced three-dimensionally, and are commonly used in courts to assist Justice. The results found point to the great precision of the replicas obtained from 3D printing, both quantitatively (metric evaluation) and qualitatively (morphological evaluation), indicating the validation of the application of additive manufacturing in Forensic Sciences, thus helping Justice and society.